2016
DOI: 10.1021/acs.jafc.5b05915
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Compounds Equivocally Influence Oxidation during Digestion of a High-Fat Beef Product, which Promotes Cytotoxicity in Colorectal Carcinoma Cell Lines

Abstract: We studied the formation of malondialdehyde, 4-hydroxy-nonenal, and hexanal (lipid oxidation products, LOP) during in vitro digestion of a cooked low-fat and high-fat beef product in response to the addition of reducing compounds. We also investigated whether higher LOP in the digests resulted in a higher cyto- and genotoxicity in Caco-2, HT-29 and HCT-116 cell lines. High-fat compared to low-fat beef digests contained approximately 10-fold higher LOP concentrations (all P < 0.001), and induced higher cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…In this context, the object of the present research is to study the efficiency of different polyphenols such as epicatechin, resveratrol and caffeic and gallic acids in the inhibition of the oxidation of linoleic acid in authentic fluid from rat small intestine [8] by monitoring the oxidation levels according to the concentration of hexanal. The effect of some hydrophilic and lipophilic phenolic compounds on the oxidation efficacy of lipids during in vitro digestion of high-and low-fat beef meat was also studied by monitoring the concentration of malonaldehyde, 4-hydroxy-nonenal and hexanal [9]. Likewise, the antioxidant effect of 2,6-di-tert-butyl-hydroxytoluene (BHT) in the oxidation of cod liver oil during in vitro digestion was demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the object of the present research is to study the efficiency of different polyphenols such as epicatechin, resveratrol and caffeic and gallic acids in the inhibition of the oxidation of linoleic acid in authentic fluid from rat small intestine [8] by monitoring the oxidation levels according to the concentration of hexanal. The effect of some hydrophilic and lipophilic phenolic compounds on the oxidation efficacy of lipids during in vitro digestion of high-and low-fat beef meat was also studied by monitoring the concentration of malonaldehyde, 4-hydroxy-nonenal and hexanal [9]. Likewise, the antioxidant effect of 2,6-di-tert-butyl-hydroxytoluene (BHT) in the oxidation of cod liver oil during in vitro digestion was demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the antioxidant effect of 2,6-di-tert-butyl-hydroxytoluene (BHT) in the oxidation of cod liver oil during in vitro digestion was demonstrated [10]. Furthermore, several studies have analyzed the effect that enrichment of certain oils with alpha-tocopherol has on their oxidation when they are submitted to digestion conditions, with controversial results [9,[11][12][13]. Finally, a comparative study of the effect of the enrichment of corn oil with alpha-and gamma-tocopherol showed that the former acts as prooxidant, which is in agreement with some of the aforementioned studies, whereas the second acts as antioxidant [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies have concluded that this latter enrichment does not cause changes in the digestion of lipid foods [10,11], or that the changes are not clear [12]. Others have found a decrease in the values of certain oxidation parameters, from which it follows that alpha-tocopherol acts as an antioxidant [2,[12][13][14][15]. Finally, other ones have reported that alpha-tocopherol acts as a prooxidant [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of protein and PUFAs was previously demonstrated during in vitro gastrointestinal digestion of meat, fish (oils), and vegetable oils . The majority of studies investigating oxidation during in vitro digestion of foods, focused on the effect of different heat treatments, different fat sources, or the effect of various additives such as myoglobin/heme‐Fe, antioxidants, or nitrite‐curing and salting, within one or a limited amount of muscle food matrices and/or oils. These studies showed that myoglobin/heme‐Fe catalyzes oxidation during digestion, and the presence of suitable antioxidants can prevent these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Muscular carnosine and anserine levels are largely species dependent, whereas levels of α‐tocopherol are also influenced by its dietary intake . Vitamin E was previously shown to delay or inhibit oxidative reactions during digestion of meat or fish . No information was found on the potential of the antioxidant dipeptides carnosine and anserine to mitigate the formation of 4‐HNE or 4‐HHE during digestion of muscle foods.…”
Section: Introductionmentioning
confidence: 99%